Evaluation of health literacy for cervical cancer and associated factors among Moroccan nursing and health technician students: An analytical cross-sectional study - Ahmed Kharbach; Mohamed Amine Baba; Rachid Razine; Abderrahman Arechkik; Amine El Aouad; Hamid Abensir; Nohayla Isra; Abderrahmane Achbani; Karim Sbai Idrissi; Radouane Belouali; Lahcen Belyamani; Majdouline Obtel (Elsevier, 2024)
Objectives: Assessing the level of health literacy among nursing and healthcare technician students at the Higher Institute of Nursing and Technical Health in Agadir, Morocco, regarding cervical cancer, and identifying associated factors. Materials and methods: This is an observational, cross-sectional, and analytical study conducted among nursing and health technician students in the 2nd and 3rd years. A self-administered health literacy assessment test was employed. Univariate and multivariate logistic regression analyses were performed to determine the factors associated with health literacy level. Results: Three hundred students were surveyed in the study. The average health literacy score was 17.1 ± 6.32, with a median score of 18 (IQR 13.50-22). Approximately one-third (30%) had a low level of health literacy. Multivariate logistic regression analysis revealed that the non-healthcare profile (OR 4.458; CI95%: 2.327-8.545; p < 0.001) was a risk factor for a low level of health literacy. Conversely, benefit from health education sessions on cervical cancer (Yes OR 0.476; CI95%: 0.248-0.918; p = 0.027), academic courses as an information source (Yes OR 0.515; CI95%: 0.274-0.968; p = 0.039), and the Web as an information source (Yes OR 0.564; CI95%: 0.323-0.985; p = 0.044) were identified as protective factors. Discussion and conclusions: The notably deficient level of health literacy regarding cervical cancer underscores the relevance of integrating a module on cervical cancer prevention into the basic education curriculum. Furthermore, it is imperative to enhance health education and awareness strategies regarding cervical cancer prevention, particularly for non-healthcare profile students. This should include targeting alternative channels such as the web and social media platforms.